2004
DOI: 10.1056/nejmoa030595
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Inactivated Intranasal Influenza Vaccine and the Risk of Bell's Palsy in Switzerland

Abstract: This study suggests a strong association between the inactivated intranasal influenza vaccine used in Switzerland and Bell's palsy. This vaccine is no longer in clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
520
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 812 publications
(530 citation statements)
references
References 26 publications
4
520
1
5
Order By: Relevance
“…This is particularly true for mucosal immunization where CT and LT have been shown to undergo retrograde transport along olfactory nerves to olfactory bulbs in the brains of mice immunized via the intranasal route (reviewed in reference 3). In humans, severe adverse reactions including Bell's palsy have been reported following intranasal immunization with LT (24,31). These concerns are perhaps less relevant for skin delivery and are likely to be site and route specific due to the proximity of key neurological pathways to the site of antigen/adjuvant application at the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for mucosal immunization where CT and LT have been shown to undergo retrograde transport along olfactory nerves to olfactory bulbs in the brains of mice immunized via the intranasal route (reviewed in reference 3). In humans, severe adverse reactions including Bell's palsy have been reported following intranasal immunization with LT (24,31). These concerns are perhaps less relevant for skin delivery and are likely to be site and route specific due to the proximity of key neurological pathways to the site of antigen/adjuvant application at the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The IN vaccination route was successful when used in humans against the influenza virus. However, the risk of Bell's palsy [27] was reported when this type of vaccine was applied in combination with E. coli toxin.…”
Section: Discussionmentioning
confidence: 99%
“…113 Some side effects have been found with the use of bacterial toxin when given intranasally, including Bell's palsy (Facial paralysis) and other adverse events related to disorders of the facial nerves. [114][115][116] It has been suggested that the central nervous system was involved in the palsy as the bacterial toxin was re-directed into the brain. 115,117 Thus, the use of LT as vaccine adjuvant is no longer recommended.…”
Section: Adjuvantsmentioning
confidence: 99%